(untitled) (Perioperaciina Medicina, 2025)
Today, thanks to technological advancements in the field of endoscopy, it is now possible to incorporate new minimally invasive endoscopic treatment methods for various gastrointestinal tract pathologies into the daily practice of endoscopists. Over the last decade, peroral endoscopic myotomy (POEM) has become a widely used modern treatment for esophageal achalasia. This technique is characterized by minimal trauma to the esophageal mucosa, high efficacy, and a short rehabilitation period due to the creation of a submucosal tunnel with myotomy of the circular muscle layer directly under the mucosa, followed by the application of endoscopic clips to the mucosotomy site. After some time, a new variation of the above method appeared in patients with epiphrenic diverticulum, called diverticular peroral endoscopic myotomy (D-POEM).This publication presents a clinical case of successful endoscopic treatment of epiphrenic esophageal diverticulum — diverticular peroral endoscopic myotomy (D-POEM). Previously, the patient conducted video gastroduodenoscopy, followed by computed tomography of the thoracic cavity with contrast. The patient was hospitalized in the surgical department of Clinical hospital “Feofaniya” as planned with a clinical diagnosis: epiphrenic diverticulum of the esophagus. After surgery, the general condition of the patient improved. In patients with epiphrenic diverticulum, this technique can be considered as an alternative to laparoscopic or open surgery, as diverticular peroral endoscopic myotomy minimizes the risk of postoperative complications and reduces the rehabilitation period.